The Application of Barokah herb and salinity on the growth of Sangkuriang catfish Clarias gariepinus Burchell, 1822 - Faulana, Arum Fahmi; Rohmah, Zuliyati (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
The demand and need for catfish is increasing along with the growth of the Indonesian population, thus requiring greater catfish production. In addition, most of the brackish water areas in Indonesia have not been optimized for freshwater fish farming. Water salinity of 4 ppt plays a role in increasing fish growth, so when combined with the use of probiotics it has the potential to optimize catfish growth. This prompted a study on the Barokah herb, a herbal probiotic developed by the Mina Rukun fish group in Gunungkidul, which was combined with a water salinity of 4 parts per thousand (ppt) for more optimal rearing of Sangkuriang catfish. This study used a Completely Randomized Design with four treatment groups: control (K), salinity 4 ppt (S), herbal probiotics Barokah Herb with a dose of 30 mL/kg feed (P), and a combination of Barokah herb and salinity (PS). Each pond contained 375 catfish as replications with a stocking density of 250 fish/m3. Data analysis was carried out using the ANOVA Test and the Tukey HSD Test as a post hoc test. The results showed that the combination of Barokah herb with a dose of 30 mL/kg feed and salinity of 4 ppt gave the best effect on the growth of Sangkuriang catfish, feed conversion ratio (FCR) of 1.001 and specific growth ratio (SGR) of 1.021. Histo-morphologically, the combination of Barokah Herb and 4 ppt salinity showed an increase in the dimensions of the villi, crypts, and tunica mucosa in the intestine and increased the dimensions skeletal muscle fascicles of the Sangkuriang catfish. This is related to the environment that is isoosmotic to the catfish's body and also the improvement of the catfish's digestive system. Keywords: catfish growth, histo-morphology, barokah herb, salinity ABSTRAK Permintaan dan kebutuhan lele semakin meningkat seiring dengan pertumbuhan penduduk Indonesia, sehingga membutuhkan produksi lele yang lebih besar. Selain itu, sebagian besar wilayah perairan payau di Indonesia belum dioptimalkan untuk budidaya ikan air tawar. Salinitas air 4 ppt berperan dalam meningkatkan pertumbuhan ikan, sehingga ketika dikombinasikan dengan probiotik, berpotensi menjadikan pertumbuhan lele lebih optimal. Hal ini mendorong dilakukannya penelitian tentang probiotik herbal Ramuan Barokah yang dikembangkan oleh kelompok ikan Mina Rukun Gunungkidul yang dikombinasikan dengan salinitas air 4 part per thousand (ppt) agar pemeliharaan ikan lele Sangkuriang lebih optimal. Penelitian ini menggunakan Rancangan Acak Lengkap dengan empat kelompok perlakuan yaitu kontrol (K), salinitas 4 ppt (S), probiotik herbal Ramuan Barokah dengan dosis 30 mL/kg pakan (P), dan kombinasi probiotik hebal dan salinitas (PS). Setiap kolam diisi 375 ekor ikan lele sebagai ulangan dengan padat tebar 250 ekor/m3. Analisis data dilakukan dengan menggunakan Uji ANOVA dan Uji Tukey HSD sebagai uji post hoc. Hasil penelitian menunjukkan bahwa kombinasi Ramuan Barokah dengan dosis 30 mL/kg pakan dan salinitas 4 ppt memberikan pengaruh terbaik terhadap pertumbuhan ikan lele Sangkuriang, rasio konversi pakan (FCR) sebesar 1,001 dan rasio pertumbuhan spesifik (SGR) sebesar 1,021. Secara histomorfologi, kombinasi Ramuan Barokah dan salinitas 4 ppt menunjukkan adanya peningkatan dimensi vili, kripta, dan tunika mukosa pada usus serta peningkatan dimensi fasikulus otot rangka ikan lele Sangkuriang. Hal ini berkaitan dengan lingkungan yang isoosmotik terhadap tubuh ikan lele dan juga perbaikan sistem pencernaan lele. Kata kunci: histo-morfologi, pertumbuhan lele, ramuan barokah, salinitas